Does sacral pulsed electromagnetic field therapy have a better effect than transcutaneous electrical nerve stimulation in patients with neurogenic overactive bladder? - Lamyaa A. Fergany (Taylor & Francis Group, 2017)
Objective: To compare the effectiveness of pulsed electromagnetic field therapy (PEMFT) and transcutaneous electrical nerve stimulation (TENS) on neurogenic overactive bladder dysfunction (OAB) in patients with spinal cord injury (SCI). Patients and methods: In all, 80 patients [50 men and 30 women, with a mean (SD) age of 40.15 (8.76) years] with neurogenic OAB secondary to suprasacral SCI were included. They underwent urodynamic studies (UDS) before and after treatment. Patients were divided into two equal groups: Group A, comprised 40 patients who received 20 min of TENS (10 Hz with a 700 s generated pulse), three times per week for 20 sessions; Group B, comprised 40 patients who received PEMFT (15 Hz with 50% intensity output for 5 s/min for 20 min), three times per week for 20 sessions. Results: In Group B, there was a significant increase in the maximum cystometric capacity (P < 0.001), volume at first uninhibited detrusor contraction (P < 0.002), and maximum urinary flow rate (P < 0.02). Conclusion: The UDS showed that the effects of PEMFT in patients with neurogenic OAB secondary to suprasacral SCI was better than TENS for inducing an inhibitory effect on neurogenic detrusor overactivity.